(3GdJMdjd GdeGdj HESJNOGe GdMGShH (B/s - (3GdOhQj, eDjO YHO GdQMefs; (3CHh RfGO, fhQ GdOjf COjHs ((3YeGf(B: s (3OQG hGFd ddfTQ hGdJhRjY(B, s, 2003)
(3jYO ehVhY GdJMdjd GdeGdj CMO GdehGVjY GdegeI aj Mbd GdGOGQI GdeGdjI hGdeMGSHI, EP ef NdGdg JJecf EOGQI GdefTCI ef JTNjU fbGW GdbhI hGdVYa aj HjFJgG GdOGNdjI hJbhje bQGQGJgG GdJehjdjI hGdGSJKeGQjI, ceG jecf Cf JSJNOeg cCMO GdCSS GdegeI aj JMOjO NjGQGJgG GdGSJQGJjLjI(B. (3LGA GdcJGH eJVefG SHY aUhd JJfGhd GdLhGfH GdCSGSjI ddJMdjd GdeGdj hJWHjbGJgG HGSJNOGe fXGe GdCcSd cCMO CfXeI GdMGShH, djSGYO GdWGdH Ydi age GdGSJNOGeGJ GdYedjI dgPG GdfXGe aj eYGdLI GdHjGfGJ GdeJhaQI hUjGZJgG HeDTQGJ cejI dJbhje GdCOGA hJQTjO GdbQGQGJ GdeGdjI(B. (3hJfGhd GdcJGH WHjYI hCZQGV GdJMdjd GdeGdj hCgejI GSJNOGe GdCfXeI GdMGShHjI aj JfXje GdHjGfGJ GdeGdjI hYQVgG HTcd jNOe YedjI GdJMdjd hGJNGP GdbQGQGJ, hJVef JMdjd hJaSjQ GdbhGFe GdeGdjI GdQFjSjI, hcPdc JMdjd GdJOabGJ GdfbOjI hcjajI EYOGO bGFeI GdJOab GdfbOj, hGTJbGb GdeDTQGJ GdJj jecf GdGYJeGO YdjgG aj Jbhje GdCfTWI GdeNJdaI ddefTCI(B. (3ceG LQi GdJQcjR aj gPG GdcJGH Ydi GdbjeI GdRefjI ddfbhO GdJj jSJNOegG GdeSJKeQ aj GMJSGH GdbjeI GdMGdjI hGdbjeI GdeSJbHdjI dOaYI hGMOI Ch dYOO ef GdOaYGJ GdeJSGhjI Ch ZjQ GdeJSGhjI aj MGd chf GdaGFOI eQcHI, hcPdc GdJQcjR Ydi OQGSI YedjI dJMdjd GdJYGOd HGYJHGQg COGI ef COhGJ GdQbGHI hJNWjW GdYdGbI Hjf GdCQHGM hGdGjQGOGJ hGdJcGdja(B. (3gPG hJfGhd GdaUd GdCNjQ JMdjd GdChQGb GdeGdjI GdeJOGhdI aj GdShb GdeGdj, heG jhaQg GdJMdjd ef eDTQGJ JSGge aj YdejI GJNGP GdbQGQGJ HGdfSHI ddeSJKeQjf hEOGQGJ GdefTBJ(B.s
Keywords: (3GdJMdjd GdeGdjs; (3GdMGShHs